2020
DOI: 10.14738/assrj.76.8194
|View full text |Cite
|
Sign up to set email alerts
|

Training of Geography Teachers for Secondary Schools at University in Uganda: An Analysis of Gulu University Teacher Trainees’ Teaching Practice.

Abstract: The changes in learner characteristics and the learning environment in the twenty first century calls for adjustments in teacher training to meet the needs of the contemporary  learners. This study analyses training of geography teachers at Gulu University with the view of assessing the application of contemporary geography teaching methodologies for the twenty first century learners. Time- series data were collected from teacher trainees’ lesson plans used during school practice running for three consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Alsharief (2018) revealed that more than 50% of the preservice teacher trainees at the teachers college in Gulf State did not have the required skills to confidently integrate technology into their lessons. Likewise, in a study to investigate how geography pre-service teacher trainees integrated digital instructional technology during school practice in three succeeding years at Gulu University, it was found that the majority did not use technology in their lessons (Nuwategeka & Odama, 2020).…”
Section: Pre-service Teacher Trainees' Competencies To Integrate Inst...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alsharief (2018) revealed that more than 50% of the preservice teacher trainees at the teachers college in Gulf State did not have the required skills to confidently integrate technology into their lessons. Likewise, in a study to investigate how geography pre-service teacher trainees integrated digital instructional technology during school practice in three succeeding years at Gulu University, it was found that the majority did not use technology in their lessons (Nuwategeka & Odama, 2020).…”
Section: Pre-service Teacher Trainees' Competencies To Integrate Inst...mentioning
confidence: 99%
“…Findings by Kisalam and Kafyulilo (2012) revealed that the mathematics and science pre-service teacher trainees of Makerere University and Dar es Salaam University College of Education would not confidently teach with technology. Nuwategeka and Odama (2020) analysed school practice with geography pre-service teacher trainees from Gulu University Facility of Science Education and Humanities for three succeeding years (2016)(2017)(2018) and it was revealed that pre-service teacher trainees did not integrate technology while 12% of the planned lessons did not even have a traditional instructional material designed. All these studies indicate that pre-service teacher trainees have inadequate skills to speed up the integration of instructional technology in ways that transform learning, but the learning process of teachers presumed to determine their competencies is still underexplored.…”
Section: Introductionmentioning
confidence: 99%